Protection against default in long term petroleum joint ventures - Eduardo G. Pereira (The Oxford Institute for Energy Studies, 2012)
Sharing costs and risks are the basic foundation of any the joint venture. However, the required financial commitments might be jeopardized either by a co-venturer who cannot afford the payment of the related costs or a co-venturer who simply chooses not to pay its share. The petroleum industry tends to rely on the forfeiture of interests as a threat to deter such behaviour but as a remedy this is often uncertain in times of its enforceability and could operate to the benefit of the defaulting party. The options to consider are collateral support provision, secured interests and cross-default options structured over wider asset interests. The recommendations which should arise out of this research intend to provide safer guidance for a long term relationship in a joint venture in the petroleum industry.
Keywords: 330; Erdölgewinnung; Joint Venture; Mineralölwirtschaft; Welt